2012
DOI: 10.1117/12.906076
|View full text |Cite
|
Sign up to set email alerts
|

Direct welding of fused silica with femtosecond fiber laser

Abstract: Development of techniques for joining and welding materials on a micrometer scale is of great importance in a number of applications, including life science, sensing, optoelectronics and MEMS packaging. In this paper, methods of welding and sealing optically transparent materials using a femtosecond fiber laser (1 MHz & 1030 nm) were demonstrated which overcome the limit of small area welding of optical materials from previous work. When fs laser pulses are tightly focused at the interface of the materials, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Further analysis of the experimental settings was performed to find the optical properties of the samples for joining. For the current experiments, the spot size (D) of the laser beam was calculated using the following equation, as described in the literature [33]:…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis of the experimental settings was performed to find the optical properties of the samples for joining. For the current experiments, the spot size (D) of the laser beam was calculated using the following equation, as described in the literature [33]:…”
Section: Sample Preparationmentioning
confidence: 99%
“…where λ is the laser wavelength and N.A is the numerical aperture values of the objective lens. Thereafter, the average fluence was estimated by employing the following equation [33]: = * * where E is the energy of single pulse, F is the frequency of laser pulses, i.e., repetition rate, and v is the laser scan speed.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Transmission measurements of the laser light allowed directly estimating the absorption through the sample ( = 8.9 • 10 ). Assuming for PMMA a thermal conductivity = 0.19W m −1 K −1 and a thermal diffusivity = 1.09 • 10 m 2 s -1 [14], the temperature growth of the substrate (ΔT 1 = 4.6×10 -3 °C ) after each laser pulse was calculated by Eq. (1).…”
Section: Mamentioning
confidence: 99%
“…Femtosecond laser processing of transparent materials, such as glasses, polymers, and crystals [1], has become a microfabrication technique of growing interest in several fields, particularly for the production of photonic and bio-medical devices since it allows direct fabrication of waveguides [2][3][4], gratings [5][6][7] and microfluidic channels [8][9][10][11][12][13].Based on this technology, several studies have demonstrated the ability of focused femtosecond laser pulses to weld similar [14,15] and dissimilar glasses [16][17][18] without the insertion of any intermediate light-absorbing layer. This innovative laser joining technique promises an easy and versatile integration of miniaturized devices.…”
Section: Introductionmentioning
confidence: 99%
“…1 In particular, direct joining techniques of glass with a focused ultra-short (femtosecond) pulsed laser beam have recently been reported. [2][3][4][5][6][7][8] In these studies, by focusing the ultra-short laser pulses at the interface between the glass substrates, the nonlinear absorption of the beam has been exploited and glass joint strength of 14.9 MPa was reported. 4 However, there are a number of shortcomings associated with this technique.…”
mentioning
confidence: 99%